Spermatogonial stem cell survival in ram lambs following busulfan treatment - Rasouli, Mohammad Hadi (Anim Reprod, 2020)
To clarify the effect of busulfan on the depletion of spermatogonial stem cells (SSCs) from shal rams testis, in the first experiment, lambs were treated by intraperitoneal injection with 4 mg/kg busulfan. In the second experiment, different concentrations of busulfan (1, 2 and 4 mg/kg) were injected directly into both sides of the left testis. The testes of 8 lambs were collected by standard castration procedure for histological analysis five weeks after the treatments and the left testis of remaining lambs were collected after eight weeks and a two-time enzymatic digestion process was used to isolate SSCs. The results showed that all rams that had received intraperitoneal injections of busulfan died. But by testicular injecting of same dose of the drug, 40% of the animals died. The testicular injection of rams with 1, 2 and 4 mg/kg of busulfan resulted in a dose dependent decrease in testis size and also spermatocytes population after 5 weeks of treatments. From the results of colony formation 8 weeks after treatment with busulfan, it can be concluded that only in 1 and 2 mg/kg of busulfan, recovery of endogenous germ cells was performed. In conclusion, the results demonstrated that intra-testicular injections of busulfan (2 mg/kg) reduced spermatocytes population in ram testis within 5 weeks of treatments, and this effect was reversible within 8 weeks of injection. However, it was not recommended to inject 4 mg/kg busulfan into the peritoneal cavity or testis of lambs based on its side effects.